New participatory proposal for the XVI Olympiad inside the Marist College of Maringa - Parana - Fassina, Valmir Augusto; Vieira, Lenamar Fiorese; Kravchychyn, Claudio; Kravchychyn, Teresinha P.; Leão, Sônia Maria Ribeiro; Vieira, José Luiz Lopes; Küster, Yara Maria (Journal of Physical Education (Maringá), 2008)
Não Possui.